(untitled) (Research, Society and Development, 2022)
This work focuses on the discussion about the nursing care provided to patients with Chronic Obstructive Pulmonary Disease (COPD) in intensive care. Objectives of the article: To analyze the care to be applied to a patient with Chronic Obstructive Pulmonary Disease in intensive care. To identify in the literature the care of patients with Chronic Obstructive Disease in intensive care. Methodology: The methodology used in the research was based on a narrative review, on works that deal with the subject addressed researched in research sites such as: Scielo, Revista Gestão & Saúde, Research, Society and Development and Revista Brasileira Clínica Médica. Conclusion: The precautions identified in the literature on COPD patients are the use of bronchodilators, which will act directly in the fight against bronchial inflammation, which are stiffened due to the creation of collagen during the defense process of cells, neutrophils and macrophages. , producing proteases, dilating them in order to facilitate breathing and better absorption of O2. Another type of care is the administration of medications by the health professional, such as β2 agonists, and short-acting ones, such as fenoterol, which will act on the sympathetic nervous system to try to dilate the airway and thus promote better breathing. In addition to these precautions, we can also use the electrical stimulation procedure, which can favor the return of respiratory activities after removal of the artificial ventilatory system. And the use of oxygen therapy that allows oxygen supplementation in order to treat and increase oxygen levels in arterial blood.